Barriocide reloaded: an updated analysis of the temporal and spatial characteristics of gang homicide in East Los Angeles - Valasik, Matthew A. (Routledge handbook of homicide studies, 2024)
This chapter examines the temporal relationship between a neighborhood’s socio-structural characteristics and gang-related homicides between 1978 and 2019 in Hollenbeck Community Policing Area within the city of Los Angeles. Using data from the decennial census, American Community Survey, and Los Angeles Police Department (LAPD) analyses are conducted estimating temporal effects, not captured by cross-sectional analyses, in examining neighborhood patterns of gang homicide. Overall, the chapter reveals gang-related homicide’s pernicious relationship with socioeconomically disadvantaged neighborhoods remains endemic, despite urban renewal and gentrification efforts.